Phase Transitions, Phase Coexistence, and Piezoelectric Switching Behavior in Highly Strained BiFeO3 Films (Adv. Mater. 39/2013). (20th October 2013) - Beekman, C.; Siemons, W.; Ward, T. Z.; Chi, M.; Howe, J.; Biegalski, M. D.; Balke, N.; Maksymovych, P.; Farrar, A. K.; Romero, J. B.; Gao, P.; Pan, X. Q.; et al.
<x xml:space="preserve">Abstract</x> A complex phase coexistence forms in epitaxial films of BiFeO3 due to the effects of epitaxial strain and temperature‐induced stresses. The work by H. M. Christen and co‐workers on page 5561 shows that the stripe patterns that form upon cooling of these atomically flat layers are a prerequisite for piezoelectric switching, i.e., the phase coexistence enables the functionality of the material. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>